PENGEMBANGAN VIDEO ANIMASI BERBASIS BUDAYA JAMBI DALAM MENDUKUNG PEMBELAJARAN DEEP LEARNING UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Silaban, Rini G.; Wardi Syafmen; Novferma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low level of students’ interest in learning mathematics, as indicated by their lack of engagement and enthusiasm during the learning process. The purpose of this study is to develop and examine the effectiveness of an animation video based on Jambi culture in supporting deep learning to enhance students’ interest in learning statistics for Grade VIII students at SMPN 1 Muaro Jambi. This study employs a research and development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects include subject-matter experts, design experts, teachers, and students of SMPN 1 Muaro Jambi. Data were collected through expert validation, practicality questionnaires, effectiveness questionnaires, students’ learning interest questionnaires, and learning outcome tests. The results of the study show that: (1) the validity test results from the subject-matter expert reached 84.61% (very valid), while the design expert validation score was 80% (valid); (2) the practicality test results indicated that the animation video was rated 83.3% (very practical) by teachers and 87.61% (very practical) by students; (3) the effectiveness test results showed that the student response questionnaire reached 89.68% (very effective), students’ learning interest increased from 48.06% (low) to 83.34% (very high), and the average learning outcomes reached 84.21% (very effective). It can be concluded that the Jambi culture-based animation video is effective in supporting deep learning and improving students’ interest in learning statistics in Grade VIII at SMPN 1 Muaro Jambi.